ANALISIS VIRTUAL REALITY PADA GAME VR CRAZY BOXING DI GAME BLINK PLAYSTATION PADANG - Rini Novita; Adinda Novidia Sari, Dimas Wahyu Pratama, Reski Budiman, Fitria Marwa, Febi Rahma Yani, Wahnada, Rid (ADISAM PUBLISHER, 2024)
This research examines the implementation of Virtual Reality (VR) technology in the boxing game